Why Cats Land on Their Feet : And 76 Other Physical Paradoxes and Puzzles - Levi, Mark, 1951- (Book collections on Project MUSE., 2012)
This book includes a collection of 77 puzzles, some clever new originals and some twists to old ones that challenge physical intuition. The puzzles run the gamut of classical mechanics, including many on fluids and rotational motion and some on heat and temperature. Every puzzle contains at least one diagram.